Optimum heat treatment to enhance the weak-link response of Y123 nanowires prepared by Solution Blow Spinning - Caffer, Ana M. [UNESP]; Chaves, Davi A.D.; Pessoa, Alexsander L. [UNESP]; Carvalho, Claudio L. [UNESP]; Ortiz, Wilson A.; Zadorosny, Rafael [UNESP]; Motta, Maycon (IOP Publishing, 2021)
Although the production of YBa2Cu3O7-δ (Y123) has been extensively reported, there is still a lack of information on the ideal heat treatment to produce this material in the form of one dimension nanostructures. Thus, by means of the Solution Blow Spinning technique, metals embedded in polymer fibers were prepared. These polymer composite fibers were fired and then investigated by thermogravimetric analysis. The maximum sintering temperatures of heat treatment were chosen in the interval 850 ◦C–925 ◦C for 1 h under oxygen flux. SEM images allowed us to determine the wire diameter as approximately 350 nm for all samples, as well as to map the evolution of the entangled wire morphology with the sintering temperature. XRD analysis indicated the presence of Y123 and secondary phases in all samples. Ac magnetic susceptibility and dc magnetization measurements demonstrated that the sample sintered at 925 ◦C/1 h is the one with the highest weak-link critical temperature and the largest diamagnetic response.
Keywords: Enhanced weak-links; Solution blow spinning; Superconducting nanowires